Nutritional Status Analysis of Toddlers (0-2 Years) for Stunting Prevention Based on E-PPGBM - Desmiany Duri, Iin; Rio Rosa Nastiti, Hilari; Widiyanto, S.Y. Didik (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2025)
Monitoring the growth of toddlers is essential as part of the minimum service standards (SPM), which must be implemented in all regions. Data related to community nutritional status is essential to determine the extent of nutritional problems in a given area, which serves as a basis for planning and implementing activities, including interventions by stakeholders, and performance evaluation. Nutrition surveillance is the process of regularly and continuously observing nutritional problems, encompassing data collection and analysis, resulting in comprehensive, accurate, and timely information on nutritional status. One of the nutrition surveillance tools developed by the Directorate of Nutrition at the Ministry of Health is known as ePPGBM (Electronic Community-Based Nutrition Recording and Reporting). E-PPGBM data can be used as important information for planning and decision-making. The study was an observational study with a quantitative approach. The research design used was cross-sectional, where the dependent and independent variables were measured simultaneously. The purpose of this study was to determine the nutritional status of infants and children under two years of age (Baduta) in Bangetayu Wetan Village in January 2023.